Estudo eletroquímico da reação de oxidação de etanol em células a combustível do tipo DEFC - (:unkn) unknown (Universidade Federal do Amazonas, 2014)
This work is about the electrochemical and spectroelectrochemical study of the oxidation reaction of ethanol for use in fuel cells operating with direct ethanol (DEFC). Ethanol as a fuel, beyond less toxic compared to methanol, has high availability in Brazil, is therefore most suitable its use as fuel. Its main limitation is the formation of reactive intermediates that strongly adsorb on the catalyst thus blocking the catalytic sites. Therefore, this project was intended to perform the study of electrochemical oxidation reaction of ethanol and its intermediates. For this purpose, we prepared binary and ternary electrocatalysts PtM/C and PtMM/C (M = Sn and Rh) by formic acid method and they were physically characterized by XRD and TEM. The electrochemical characterization was carried out in acidic media using cyclic voltammetry and chronoamperometry. Monitoring the formation of products and intermediate species formed during the electrooxidation of ethanol was done by in situ FTIR. Finally, polarization curves were performed to determine the performance of the unitary fuel cells. The physical characterization data showed particle sizes from 1.5 to 5 nm with good dispersion of catalytic material on carbon support. The electrochemical characterization revealed features for binary and ternary alloys, with no defined regions, compared to pure platinum. The FTIR results revealed the formation of CO2 and acetic acid as major products and the increasing concentration possibly leads to greater formation of acetaldehyde. The data in the unit cell showed higher performance for PtSn/C with a power density of approximately 23 mW cm-2.
Keywords: Oxidação de etanol; Alcool etílico; Reações químicas; Oxidation of ethanol; Ethyl alcohol; Chemical reactions; CIÊNCIAS EXATAS E DA TERRA: QUÍMICA